Novel miRNA-SSRs for Improving Seed Hardness Trait of Pomegranate (Punica granatum L.) - Patil, Prakash Goudappa; Singh, Nripendra Vikram; Bohra, Abhishek; Jamma, Shivani; N, Manjunatha; C, Venkatesh S.; Karuppannan, Dhinesh Babu; Sharma, Jyotsana; Marathe, Rajiv A. (Frontiers in Genetics, 2022)
Present research discovered novel miRNA-SSRs for seed type trait from 761 potential precursor miRNA sequences of pomegranate. SSR mining and BLASTx of the unique sequences identified 69 non-coding pre-miRNA sequences, which were then searched for BLASTn homology against Dabenzi genome. Sixty three true pri-miRNA contigs encoding 213 pre-miRNAs were predicted. Analysis of the resulting sequences enabled discovery of SSRs within pri-miRNA (227) and pre-miRNA sequences (79). A total of 132 miRNA-SSRs were developed for seed type trait from 63 true pri-miRNAs, of which 46 were specific to pre-miRNAs. Through ePCR, 123 primers were validated and mapped on eight Tunisia chromosomes. Further, 80 SSRs producing specific amplicons were ePCR-confirmed on multiple genomes i.e. Dabenzi, Taishanhong, AG2017 and Tunisia, yielding a set of 63 polymorphic SSRs (polymorphism information content ≥0.5). Of these, 32 miRNA-SSRs revealed higher polymorphism level (89.29%) when assayed on six pomegranate genotypes. Furthermore, target prediction and network analysis suggested a possible association of miRNA-SSRs i.e. miRNA_SH_SSR69, miRNA_SH_SSR36, miRNA_SH_SSR103, miRNA_SH_SSR35 and miRNA_SH_SSR53 with seed type trait. These miRNA-SSRs would serve as important genomic resource for rapid and targeted improvement of seed type trait of pomegranate.